Stare i nowe polskie piosenki i pieśni patriotyczne - Piotr Kładoczny (Język. Religia. Tożsamość, 2021)
The article is devoted to old and new Polish patriotic songs. It contains an analysis of the content of the collected works. The old songs were uplifting in nature and were very important for national culture. They were used to shape identity and build community, and at the same time to communicate important events. They express love for the homeland, proclaim its beauty and the need to fight for the maintenance or recovery of freedom. The new songs were created after 1983 and are already part of popular culture. They are highly individualized and express the emotional personal commitment of the creator. In addition, they move away from religious themes. Modern patriotic songs consist of four currents: traditional, new attitudes, social and historical. Traditional and historical currents are the closest in value to old patriotic songs. The current of new attitudes becomes a place of searching for an individual reference to patriotism. The social trend registers reality and is sometimes used to take a critical look at what is currently happening in Poland.